(3TQM CHjGJ aj GdXGAGJs - (3CHh GdWGgQ ESeGYjd Hf CMeO Hf RjGOI Gddg GdJLjHi , GdeYQha HGdHQbis; (3CHh GdYHGS CMeO Hf YeGQ GdebQjs
(3ChdgG (B:s
(3bGd GdEeGe CHh GdWGgQ gPg CHjGJ fXegG CHh GdYHGS CMeO GHf YeGQ GdebQF ai LejY CLfGS GdXGAGJ s
(3BNQgG (B:s
(3aCfRd Gddg SHMGfI(B: " (3hEPG QChG JLGQI Ch dghkG EfaVhG EdjgG hJQchc bGFekG, bd eG YfO Gddg NjQ ef Gddgh hef GdJLGQI, hGddg NjQ GdQGRbjf (B" (3hbGd BNQ ai hUa QhVI CgOi Edjc GdeSc aV NJGeg hGdYfHQ GdYOfi ai GdCQOGf GfJgi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B_ (3GdQHGW (B(505(3O(B) s
Keywords: (3GddZIs